(untitled) (Western European Journal of Medicine and Medical Science, 2026)
This article discusses the surgical treatment of thyroid cancer, including indications for surgery, selection of the extent of surgical intervention, as well as postoperative complications and their prevention. The main treatment method for thyroid cancer is thyroidectomy (total or partial), and when necessary, lymph node dissection is performed. The effectiveness of surgical techniques, treatment strategies depending on the stage of the disease, and patient rehabilitation issues are analyzed